PENATALAKSANAAN HOLISTIK PADA NELAYAN LAKI-LAKI USIA 40 TAHUN DENGAN LOW BACK PAIN MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS RAWAT INAP SUKARAJA - Farizy, Diaru Fauzan; Syamhudi, Muhammad Farras Afif; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2024)
Low Back Pain (LBP) is a musculoskeletal disorder caused by poor body activity. Data for the number of LBP sufferers in Indonesia is estimated at 11.9%. Work-related lower back pain is often reported in workers who perform certain physical actions. Applying the principles of family medicine services and carrying out holistic management based on a framework for solving patient problems with a patient-centered, family focused and community oriented approach based on Evidence Based Medicine. This study is a case report study. Primary data was obtained through auto-anamnesis, physical examination and home visits, filling in the family folder, completing family data, psychosocial and environmental data. The assessment is carried out based on a holistic diagnosis of the beginning, process and end of the study quantitatively and qualitatively. Patient Mr. A, male, 40 years old, works as a fisherman and has a main complaint of lower back pain since approximately one year ago but the pain has worsened in the past one week. The pain improves when resting and gets worse when the patient is active. The patient was diagnosed as Low Back Pain. Pharmacological and non-pharmacological interventions were carried out in the form of education regarding ergonomic body positions and exercise to reduce complaints of lower back pain. The diagnosis and management of Low Back Pain in this patient has been carried out in a holistic, patient-centered, family approach and based on several theories and the latest research.